(untitled) (Poornaprajna International Journal of Management, Education & Social Science (PIJMESS), 2024)
Purpose: This study aims to investigate the impact of leadership and peer support on stress management among bank employees in Kerala, focusing on how these factors influence stress levels and overall job satisfaction in a high-pressure environment. Methodology: The research employs Structural Equation Modeling (SEM) to analyze data collected from a sample of 464 employees across various banks in Kerala. A structured questionnaire was utilized to assess perceptions of leadership style, peer support, and stress management. The data was evaluated using statistical techniques, including Confirmatory Factor Analysis (CFA), Exploratory Factor Analysis (EFA), and regression analysis. Results/Analysis: The findings reveal that both leadership style and peer support significantly contribute to effective stress management. Leadership that provides clear direction and emotional support, along with robust peer networks, results in lower stress levels and higher job satisfaction. This study confirms that leadership and peer support have a substantial impact on stress management outcomes, enhancing overall performance and employee well-being. Originality/Value: The paper offers actionable insights for banks to develop strategies that leverage both leadership and peer support to create a supportive work environment. This study adds value by providing empirical evidence on the combined effects of leadership and peer support on stress management in the banking sector, particularly in the context of Kerala. Type of Paper: Empirical Research